Analytical study of the concepts of health education in the science book for the fourth grade of basic education in the Syrian Arab Republic - Ammar, Sam; Emad, Hasan; Ktene, Foton (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The present study aimed at determining the degree of availability of the concepts of health education in the science book for the fourth grade in the Syrian Arab Republic. Therefore, the researcher designed an analysis list which included seven main fields, under which 44 subcategories related to health education. , And the most important findings of the present study are the following: - Focus attention on the health of skeletal and muscular, and nervous system. - low interest rate of provision of emergency health instructions, fitness, and proper nutrition appropriate for the fourth grade student. - low interest in healthy environment, and its reflection on human health. - omission of the science book for a large section of the main categories in addition to the sub-categories included in the list of the analysis of the concepts of health education. - There are statistically significant differences in the frequency distributions registered in the concepts of health education in the science book for the fourth grade according to the basic variable of the registration unit (idea, image, activity).